Pengaruh Lingkungan Kerja dan Disiplin Terhadap Kinerja Pegawai pada Bagian Administrasi Pemerintahan Umum Sekretariat Daerah Pematangsiantar - Eka Pratiwi Septania Parapat; Wiranto Sinaga; Eve Ida (Politeknik Ganesha Medan, 2020)
An employee who has a good and high performance can support the achievement of organizational goals. Human resource issues become the spotlight and foundation of the organization. The formulation of the problem in this study is the work environment and discipline of cooperation on the performance of employees in the General Government Administration of the Pematangsiantar City Secretariat. This study aims to determine the effect of work environment and work discipline on employee performance in the General Government Administration of Pematangsiantar City Secretariat. The research design used by the author is field research, where the research is carried out in the General Government Administration of the Pematangsiantar City Secretariat, the population is the employees of the Pematangsiantar City Secretariat General Government Administration. The sampling technique used a saturated sample using the entire population as a research sample, amounting to 37 employees. The data analysis technique uses multiple regression, hypothesis testing, coefficient of determination. The results showed that the work environment and work discipline have a positive effect on the performance of employees in the General Government Administration of the Pematangsiantar City Secretariat